2021
DOI: 10.1038/s41598-021-90364-7
|View full text |Cite
|
Sign up to set email alerts
|

Brainwide functional networks associated with anatomically- and functionally-defined hippocampal subfields using ultrahigh-resolution fMRI

Abstract: The hippocampus is critical for learning and memory and may be separated into anatomically-defined hippocampal subfields (aHPSFs). Hippocampal functional networks, particularly during resting state, are generally analyzed using aHPSFs as seed regions, with the underlying assumption that the function within a subfield is homogeneous, yet heterogeneous between subfields. However, several prior studies have observed similar resting-state functional connectivity (FC) profiles between aHPSFs. Alternatively, data-dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The anatomic side of memory is mainly situated in the hippocampus [25]. It is a neural structure with complex efferent and afferent connections with various brain cortices, that exerts a fundamental role in learning [26]. Consequently, STM and LTM are archived mainly in the hippocampus, but also in other cortex regions.…”
Section: Cognitive Functions Memory and Agingmentioning
confidence: 99%
“…The anatomic side of memory is mainly situated in the hippocampus [25]. It is a neural structure with complex efferent and afferent connections with various brain cortices, that exerts a fundamental role in learning [26]. Consequently, STM and LTM are archived mainly in the hippocampus, but also in other cortex regions.…”
Section: Cognitive Functions Memory and Agingmentioning
confidence: 99%
“…Recent studies suggest that hippocampal subfields may not be distinct functional units. For instance, Chang et al 72 report that the functional organization within the hippocampus is more intricate than what lamellar anatomical divisions might capture. For one, the posterior and anterior hippocampus may be biased towards pattern separation and completion, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus exhibits cytoarchitectural differences among subfields [14], which may lead to functional distinctions across them. Connectomic and neurophysiological studies have shown differences in the regions they connect to and the directions of connections [15,16]. These differences may be due to genetic determinants, as hippocampal subfields have unique genetic correlates that associate with specific biological processes [17,18].…”
Section: Introductionmentioning
confidence: 99%